A convenient verification method of the entrance photo-neutron dose for an 18 MV medical linac using silicon p-i-n diodes. (November 2017) - Gracanin, Vanja; Guatelli, Susanna; Cutajar, Dean; Cornelius, Iwan; Tran, Linh T.; Bolst, David; Preston, Rhys; Gupta, Rashmi; Yuen, Johnson; Petasecca, Marco; Lerch, Michael; Prevertaylo, Vladimir; et al.
Abstract: Electron Linear Accelerators (linacs) used in radiotherapy treatments produce undesired photo-neutrons when they are operated at energies above 10 MeV. (Neutron Contamination from Medial Electron Accelerators, 1984). These photo-neutrons contaminate the therapeutic beam and increase dose equivalent delivered to patients. In this work, the neutron entrance dose for an 18 MV Varian Medical linac was measured using passive silicon p-i-n diodes. These detectors were calibrated in separate photon, electron and neutron fields. The silicon p-i-n diode detectors have shown excellent discrimination between fast neutron and photon radiation, with sensitivity to fast neutrons being ≈4000 times higher than to photons from a 60 Co source in terms of absorbed dose to tissue. The neutron tissue absorbed dose was studied both on the surface and inside a cubic solid water phantom, both experimentally and also using Geant4 Monte Carlo simulations. The silicon p-i-n diodes were found to be useful for quick estimation of the fast neutron tissue dose and dose equivalent in pulsed, mixed radiation fields produced by a medical linac. Highlights: Investigation of the effect of different p-i-n diode geometry for neutron detection. Development of a detector readout system for quick estimation of the fast neutron dose and neutron dose equivalent. Geant4 simulation study of a p-i-n diode response to electrons and neutrons, on the surface and inside a solid water phantom. Study of the photo-neutron dose equivalent on the surface and with depth inside a cubic solid water phantom.